From pre-competition prep to recovery: analysing cyclists' dietary choices and gastrointestinal health in an endurance competition - Mónica Castillo-Martínez; Rubén Jiménez-Alfageme; César Iván Ayala-Guzmán; Sergio Martín Hernández; Isabel Sospedra; Aurora Norte; David Romero-García; Lucía Herrera-Puche; José Miguel Martínez Sanz (Revista Española de Nutrición Humana y Dietética, 2025)
Introduction: In recent years, long-distance events and mountain biking or MTB have seen a growth in both the number of events organised and  number of participants. In this type of endurance event, proper nutritional and hydration planning is essential to maintain optimal sporting performance and reduce the incidence of gastrointestinal problems. The aim of this study is to determine the dietary intake and compliance with nutritional recommendations of athletes in two endurance competitions at different times: pre-competition, during competition and post-competition, and as well, assess the incidence of gastrointestinal discomfort.